Time-dependent biphasic modulation of human BDNF by antidepressants in neuroblastoma cells - Musazzi Laura; Tardito Daniela; Tiraboschi Ettore; Donnici Lorena; Racagni Giorgio; Popoli Maurizio (BMC Neuroscience, 2008)
Abstract Background Recent rodent studies reported that antidepressant treatments affect the expression of brain-derived neurotrophic factor (BDNF) mRNA in a way that is dependent on treatment duration, by selective modulation of different BDNF transcripts. However, no data are available for the human BDNF gene. We studied the effect of different antidepressants on BDNF mRNA expression in human neuroblastoma SH-SY5Y cells. Results Cultured cells were treated with the antidepressants fluoxetine, reboxetine and desipramine for different time lengths (6, 24, 48 hours). Expression of total BDNF mRNA was analyzed by reverse transcription PCR and levels of different BDNF transcripts were detected by hemi-nested PCR with specific primers. Short-term treatment (6 hours) with reboxetine or desipramine reduced total BDNF, whereas long-term treatment (48 hours) significantly increased total BDNF mRNA levels. These changes were accounted for by differential regulation of BDNF IV and VIa/b transcripts. Fluoxetine showed no significant effects. Conclusion This is the first study showing biphasic changes in the expression of total and specific BDNF transcripts in human cells following antidepressant treatments. These findings suggest that biphasic induction of BDNF by antidepressants could be a feature common to rodents and humans and encourage the use of SH-SY5Y cells as a tool for investigation of drug effects on human genes.